Self-Recovery Practices of Ukrainian Civilian at the Beginning of the War: Subcultural Differences - Tytarenko , Tetiana (Insight: the psychological dimensions of society, 2024)
The purpose is to determine the configurations of self-preservation and recovery practices typical for representatives of different age subcultures under martial law. Methods. The sample included 169 civilians of Ukraine. Data collection was carried out in March – May 2022. The key research method was an online narrative on the topic “My life during the war”. The data were processed using descriptive, interpretive analysis, and descriptive statistics. Practices were coded according to the focus of efforts to overcome negative emotional states. Results. Representatives of different age subcultures turned to the following self-recovery practices: family-communicative, work/educational, household-relaxation, patriotic, meditative-spiritual, informational-analytical, counselling-therapeutic, volunteer, and reflective-developmental; however, the ratio of these practices and their content in each subculture was unique. The individual-oriented health-care practices of the youth subculture were aimed at reducing their suffering, the interpersonally oriented practices of representatives of the early adulthood subculture were focused on the desire to preserve the life and health of loved ones, and the socially oriented practices in the mid-late adulthood concentrated on the dominance of the value of selflessness activities, realizing the need for one’s own contribution to the approach of victory. Discussion and conclusions. The hypothesis about the self-restoration function of practices as a form of daily behavior is confirmed. The hypothesis regarding the specification of access to self-help practices in different age subcultures, which allows for the stabilization of the emotional state in one’s own way, accept the external and internal restrictions determined by war conditions, rethink losses, needs, intentions, make adjustments to self-identification and sense-making, has received a certain evidence base. It is shown that the expansion of the range of health care practices implies a willingness to adequately and creatively deal with the military present; a willingness to accept help from others and provide support to one’s environment; a willingness to accept and support oneself, to improve one’s own professional and self-regulatory capabilities. Focusing on a person’s subcultural characteristics will contribute to the targeted formation of such readiness and improve the targeting of educational, correctional, and rehabilitation interventions.
Keywords: Array; Array; Array; Array; Array